Method of increasing vaccination effectiveness using pre-vaccination therapy with vitamin D3 (Information Letter) - Volianskyi, Andriy; Smilyanskaya, Maya; Didorenko, Tatiana; Kuchma, Iryna (Annals of Mechnikov's Institute, 2025)
The following scheme of pre-vaccination vitamin therapy with vitamin D3 is proposed: two weeks before vaccination, take 2000 IU of vitamin D3 daily. The use of this method optimizes the effect of vitamin D3 on the functioning of both nonspecific defense mechanisms and adaptive immunity, which in turn contributes to the rapid and intensive production of specific antibodies in high titers and an increase in the duration of preservation of intense specific immunity.